Hubungan Kejadian Burnout Dengan Motivasi Kerja Perawat Pelaksana Di Rumah Sakit Bhayangkara Kota Bengkulu - Pebriani, Emi; Ramlis, Ravika (Utami Publisher, 2025)
The primary role of a nurse is to care for, advocate for, and support patients through healthcare programs. This can sometimes lead to burnout, especially if the nurse lacks motivation within their work environment, either from their colleagues or superiors. This requires motivation, which plays a crucial role in every nursing job, as motivation is a strong drive, desire, or interest within oneself to achieve a specific desire, goal, or goal. The purpose of this study was to determine the relationship between burnout and nurse work motivation at Bhayangkara Hospital, Bengkulu. This study used a quantitative analytical approach with a cross-sectional approach. The population was 53 and the sample size was 35. The sampling technique used was non-probability sampling with the accidental sampling method. Data analysis used the Chi-Square statistical test. The results of the study showed a relationship between burnout and nurses' work motivation, with a p-value of 0.004 (p<0.005). The conclusion of this study is that there is a relationship between burnout and nurses' work motivation at Bhayangkara Hospital, Bengkulu. Suggestions are that several health promotion efforts are needed to increase nurses' motivation and prevent burnout in the workplace.